Method for analyzing the vulnerability of water resources in an unstable environment based on the entropy approach - Bezsonnyi , V. L. (Man and Environment. Issues of Neoecology, 2023)
Purpose. The synthesis of the method of analyzing the vulnerability of water resources based on the entropy of the connection based on the determination of the factors of the water system, considering the relationship between the anthropogenic socio-economic system and the "man-environment" system and the analysis of the transformation processes of the water system in a changing environment. Results. The mechanism of vulnerability of water resources in a changing environment is analyzed. The structure of the vulnerability of water resources is established based on sensitivity, natural resistance and artificial adaptation by analyzing the four states of the water system: the sensitive state, the impaired state, the recovery state and the equilibrium state, and accompanying transformation processes. A method for analyzing the vulnerability of water resources based on contact entropy is proposed, which extends the concept of contact entropy. The degree of vulnerability of water resources to the changing environment can be divided into five levels with 11 indices: low (I), insignificant (II), moderate (III), high (IV) and extreme (V). Calculation of the contact entropy shows an approximate value of the contact entropy S with a range of (–1.314; 1.314). This interval is divided into five parts: [0.877; 1.314), [0.292; 0.877), [−0.292; 0.292), [−0.877; −0.292), (−1.314; − 0.877), indicating low (I), insignificant (II), moderate (III), high (IV) and excessive (V) degrees of vulnerability of water resources, respectively. Conclusions. The state of a water system usually changes from impaired to restored due to natural factors, followed by a transition from a state of restoration to a state of equilibrium mainly due to artificial factors. The first is defined as natural resilience, and the second as artificial adaptation. The results of this mechanism offer a necessary understanding of the vulnerability of water resources in a changing environment, the mechanism of the transformation process between the four states is the focus of further research.